Quality of records keeping by undergraduate dental students in Ibadan, Nigeria (2012)
Background: Recording the interaction between a patient and the dentist is of primary importance in dental practice. The completeness of recordings of undergraduate students, often inadequate, has been found to subsequently impact on the quality of dental care offered by professionals. Once identified, correcting the inadequacies has also been shown to improve the quality of dental practice. Objective: We aimed to evaluate the quality of records keeping by dental students in Ibadan, Nigeria. Method: A retrospective review of records of patients seen by dental students, at the clinics of the dental school in Ibadan, Nigeria, over a six months period was conducted. The charts were reviewed for: demographic data, medical and dental history, clinical findings, diagnosis, treatment plan and note on informed consent. Assessment of the quality of data obtained was done using a modified CRABEL’s scoring system. Results: A total of 318 case files were retrieved for this study. The median modified CRABEL score was 95%, with a range of 65 to 95%. Eighty-two recordings (25.2%) had a score < 90%, while 236 recordings (74.2%) had a score > 90%. The most frequently unrecorded data was written consent in all the charts, followed by procedure done with the documentation absent in 20.4%. All the supervisors signed at the end of the consultation. Conclusion: The quality of records keeping by dental undergraduates is fair but there is a need to emphasize deficient areas and improve upon the quality of record keeping